An Overview Of The Metrics Used In Appointment Scheduling Systems And Their Classification - Kumar Mishra, Rakesh; Sharma, Geetanjali (Journal of Neonatal Surgery, 2025)
In this Study are reviewed that are used to assess how well appointment scheduling systems performing. The English-language papers is searched from the The Google Scholar search engine and the PUBMED databases, WEB OF SCIENCE, SCOPUS, we classified assessment metrics based on queuing theory. Findings: 85 papers, for in-depth examination. We categories appointment scheduling system evaluation measures in addition to their definition and usage frequency. There are 24 measurements in all, with 12 (%50), 7 (%29), and 5 (%21) having to do with the arrivals (patient), clinic line (patient), and server (physician) categories, respectively. The majority of metrics is patient-related, which may emphasize how crucial the patient's viewpoint is when assessing appointment scheduling systems.